Resolving the 1886 White Terraces riddle in the Taupō Volcanic Zone - Bunn, A. Rex (Frontiers in Earth Science, 2023)
Of the Seven Wonders of the Ancient World only the Great Pyramid of Giza survives. Yet there is another, older than the seven─ found and then lost again in the nineteenth century and once more located by the research herein: the White Terraces (the indigenous name is Te Tarata) of the Taupō Volcanic Zone in New Zealand. The greatest geoscience and tourist attractions in the southern hemisphere were the siliceous Pink and White Terraces. European, American and British tourists bypassed calcareous terraces at Saturnia, Yellowstone and Pamukkale for the long sea voyage down to New Zealand. The 1886 Mt Tarawera eruption buried the siliceous terraces, decimating their indigenous owners and their tourism. An eruption crater lake now occupies much of the Rotomahana Basin in the Taupō Volcanic Zone leading to assumptions the Terraces were lost, but no evidence was produced. The indigenous Māori owners did not believe they were lost. Controversy ensued. It is of economic and cultural importance as well as of scientific interest, that this controversy is resolved. In 2011, a joint New Zealand-American project claimed to have found the Pink and White Terraces underwater in the crater lake but produced no sinter samples. Recently their claims were refuted. In Europe, terrestrial survey documents were unearthed, including compass bearings to the terraces by the German geologist Ferdinand Hochstetter. His survey records were digitally repatriated and his 1859 survey was reconstructed, showing the terrace springs lay outside the eruption crater. This renewed research in the Rotomahana Basin which now resolves the controversy. By studying topography and with the aid of Māori navigation knowledge the geographic coordinates for the White Terraces are triangulated. These lie on land, on the shoreline outside the 1886 crater. Surprisingly, this evidence demonstrates the White Terraces could have been located in 1886 after the eruption by observation of the Rotomahana Basin with mapping available since 1864. Exploration and excavation of the Terraces are now possible. Even if degraded by the 1886 eruption, the White Terraces may earn a World Heritage listing and a second life in global tourism.